Memória do Santo Daime na Paraíba: vinte anos de histórias ao Som e na Luz da Floresta - Nascimento, Dávila Maria da Cruz Andrade (2014)
Santo Daime is a religion that makes use of entheogenic drink Ayahuasca in their rituals. Formed in the mid-1930s in the city of Brasiléia, State of Acre, north of Brazil, founded by Raimundo Irineu Serrawho, borned in Maranhão, he migrated to the Amazon rainforest in the waves of the rubber boom. From Vila Ivonete quarter, with rural ares and strong Northeast presence, Santo Daime follows a script messia nic characteristics around the forest under the charismatic leadership of Sebastião Mota de Melo, and thence to the world. This research seeks to understand how, in the process of expanding to large urban centers and abroad, the Santo Daime comes to State of Paraíba and brings together the first group of followers who formed the first church in the Northeast, and other groups from Paraíba. We aimed to know which components of this land provided the establishment of this religious following in this field, the formation of Paraiba's daimista people, their characteristics and trends. As the main source of research subjects of this field actors of that history that revitalize memory in reports during the interviews, biased in Oral History, and their life experiences as followers of this cult. Anchored at the anthropological category known as participant observation or even observant participation, the research will marking its contours in the construction of the Santo Daime in Paraíba, gateway of this religion in the Northeast, and its development in the region memory. In Paraíba there are four groups or churches of Santo Daime, this research sought to identify the participants' narratives historical and cultural elements that make up this religious denomination in Paraiba field. This is an original study for the presence and memory of that religious group in Paraíba and Northeast regions.